Predicting Success of Range-Expanding Coral Reef Fish in Temperate Habitats Using Temperature-Abundance Relationships - Booth, David J.; Beretta, Giglia A.; Brown, Luke; Figueira, Will F. (Frontiers in Marine Science, 2018)
An 18-year database of coral reef fish expatriation poleward in South East Australia was used to estimate persistence of coal-reef fish recruits on temperate reefs. Surveys have identified over 150 coral-reef fish species recruiting to temperate reefs at latitudes of 340S (Sydney) and 60 species to 370S (Merimbula) with 20 and 5 species respectively overwintering in at least one year over the study duration. We developed indices of vulnerability of key species to drops in water temperatures, by relating drops in abundances of species to temperature drops. Twenty species were ranked according to their temperature vulnerability. Overall, the families Chaetodontidae (butterflyfishes), Acanthuridae (surgeonfishes), Labridae (wrasses) and Pomacetnridae (damselfishes) had similar cold-water tolerance. However, there was considerable variability within families, for instance in the Pomacentridae, species from the genus Abudefduf appeared to have better cold-temperature tolerance than the other species. Predicted minimum overwintering temperature varied from 15.6C to 19.8C, with some species showing lower Tzero at Merimbula, the more poleward location. There was general concordance between a species’ tolerance to cold-water and its tendency to occur as an overwinter but also notable exceptions. So while this work demonstrates the potential utility of tolerance to seasonal temperature drops as a means to predict range expansion capacity of vagrant species, the exceptional cases serve to highlight alternative factors. Specifically, tolerance to seasonal cooling of water is not the only important factor when predicting the range expansion capacity of a species. Factors affecting the general abundance of the vagrants, such as habitat suitability and competitor/predator environments will also be critical where overwinter survival becomes a lottery.